Comparison of kinetic and equilibrium reaction models insimulating the behavior of porous media - Kowalsky, Michael B.; Moridis, George J. (Lawrence Berkeley National Laboratory, 2006)
In this study we compare the use of kinetic and equilibriumreaction models in the simulation of gas (methane) hydrate behavior inporous media. Our objective is to evaluate through numerical simulationthe importance of employing kinetic versus equilibrium reaction modelsfor predicting the response of hydrate-bearing systems to externalstimuli, such as changes in pressure and temperature. Specifically, we(1) analyze and compare the responses simulated using both reactionmodels for natural gas production from hydrates in various settings andfor the case of depressurization in a hydrate-bearing core duringextraction; and (2) examine the sensitivity to factors such as initialhydrate saturation, hydrate reaction surface area, and numericaldiscretization. We find that for large-scale systems undergoing thermalstimulation and depressurization, the calculated responses for bothreaction models are remarkably similar, though some differences areobserved at early times. However, for modeling short-term processes, suchas the rapid recovery of a hydrate-bearing core, kinetic limitations canbe important, and neglecting them may lead to significantunder-prediction of recoverable hydrate. Assuming validity of the mostaccurate kinetic reaction model that is currently available, the use ofthe equilibrium reaction model often appears to be justified andpreferred for simulating the behavior of gas hydrates, given that thecomputational demands for the kinetic reaction model far exceed those forthe equilibrium reaction model.